2021
DOI: 10.1136/gpsych-2021-100523
|View full text |Cite
|
Sign up to set email alerts
|

Cut it out or wait it out? Case series of middle fossa arachnoid cysts presenting with psychiatric symptoms and a discussion of the ethics of neurosurgical management

Abstract: Arachnoid cysts have been linked to neuropsychiatric morbidity. We describe two patients presenting with dissociative and manic symptoms believed to be associated with middle fossa arachnoid cysts. They were managed medically and remitted eventually, but symptoms were resistant. We briefly review the literature to discuss mechanisms by which cysts could cause symptoms and consider whether neurosurgical management would be appropriate. Although neurosurgery can be considered, its role is currently limited by pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The article by Steyn et al [ 46 ] discussed the possible causes of psychiatric symptoms due to arachnoid cysts and concluded that there was plausible evidence that middle cranial fossa cysts caused neuropsychiatric symptoms. At the same time, their article explored whether psychiatric symptoms could be an indication for surgery for arachnoid cysts, and concluded that the decision for surgery should be based on a consensus between the patient, psychiatrist, and neurosurgeon.…”
Section: Discussionmentioning
confidence: 99%
“…The article by Steyn et al [ 46 ] discussed the possible causes of psychiatric symptoms due to arachnoid cysts and concluded that there was plausible evidence that middle cranial fossa cysts caused neuropsychiatric symptoms. At the same time, their article explored whether psychiatric symptoms could be an indication for surgery for arachnoid cysts, and concluded that the decision for surgery should be based on a consensus between the patient, psychiatrist, and neurosurgeon.…”
Section: Discussionmentioning
confidence: 99%